Decreased DUSP26 Expression Promotes Malignant Behavior in Glioblastoma Cells via Deregulation of MAPK and Akt Signaling Pathway - Chen, Jiajia; Zeng, Yuecan; Wu, Rong; Xuan, Ying; Jiang, Min; Teng, Hao (Frontiers in Oncology, 2021)
Purpose: Dual-specificity protein phosphatases 26 (DUSP26) is a recently identified phosphatase enzyme that regulates MAPK and Akt signaling pathways. The role of DUSP26 in the development and prognosis of high-grade gliomas (HGGs) and primary glioblastoma (GBM) has remained unclear and was the focus of this study. Materials and Methods The prognostic value of DUSP26 was assessed using retrospective analyses using online data sets and tissue microarray of HGGs. U251 and U87 cells modified to overexpress DUSP26 were utilized to study the role of DUSP26 in cell growth, migration, and cell apoptosis analyzed by CCK-8 assay, clonogenic, transwell migration, and TUNEL, respectively. The phosphorylation of proteins in MAPK and Akt signaling pathways was assayed by Western blot and immunofluorescence assays. Results Analyses using available online data sets and tissue microarray showed that DUSP26 is down-regulated in high-grade gliomas and GBM as compared to normal brain. Stratification of glioma patients based on DUSP26 expression level showed an inverse correlation between DUSP26 expression and patient survival. At the cellular level, DUSP26 overexpression led to decreased cell proliferation, migration, and senescence in U251 and U87 cells, whereas apoptosis was increased as compared to corresponding controls. Interestingly, the biologic effects of DUSP26 overexpression were associated with the dephosphorylation of proteins in the MAPK and Akt signaling pathways. Conclusions These findings suggest that the loss of DUSP26 expression, seen in a subset of high-grade gliomas and GBM patients, facilitates malignant behavior; and with inverse correlation between its expression levels with patient survival. DUSP26 can serve as an independent prognostic factor.